Annotated record and detailed features of Mn deposits from R/V Bosei Maru Cruise GDP-8 stations - Shiki, Tsunemasa; Harada, K; Yoshida, H; Okuda, Y; Aoki, H; Hansen, Henry; Matsuo, K; Kobayashi, Kazuo; Takayama, Toshiaki (Supplement to: Shiki, T et al. (1974): Basaltic tuff obtained at the Daini-Kinan Seamount and acidic plutonic rocks collected at the Komabashi-Daini Seamount (in Japanese). Journal of the Geological Society of Japan, 80(10), 489-491, https://doi.org/10.5575/geosoc.80.489, 1974)
During the GDP-8 cruise of R/V Bosei-Maru, scientists from the Tokai University surveyed the Kinan seamount chain and the Kyushu-Palau Ridge in the Phillippine Sea. They dredged manganese nodules and ferromanganese crusts formed around basaltic tuff rocks and acid plutonic rock pebbles.